2020
DOI: 10.3390/cells9061525
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral versus Circulating Lymphoid Cells as Predictive Biomarkers in Lung Cancer Patients Treated with Immune Checkpoint Inhibitors: Is the Easiest Path the Best One?

Abstract: The molecular and cell determinants that modulate immune checkpoint (ICI) efficacy in lung cancer are still not well understood. However, there is a necessity to select those patients that will most benefit from these new treatments. Recent studies suggest the presence and/or the relative balance of specific lymphoid cells in the tumor microenvironment (TEM) including the T cell (activated, memory, and regulatory) and NK cell (CD56dim/bright) subsets, and correlate with a better response to ICI. The analyses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 89 publications
(114 reference statements)
0
15
0
Order By: Relevance
“…However, ICI treatments are only effective in approximately 20% to 30% of cancer patients whose tumors are generally hot tumors with a high degree of T cell infiltration and high immune checkpoint expression ( 3 ). The majority of patients have no response or are resistant to the treatment, which is largely associated with cold tumors with few or absence of T cells, low tumor mutational burden, and poor antigen presentation ( 3 ). Furthermore, the efficacy varies among different tumor types, which further complicates treatment strategy.…”
Section: Introductionmentioning
confidence: 99%
“…However, ICI treatments are only effective in approximately 20% to 30% of cancer patients whose tumors are generally hot tumors with a high degree of T cell infiltration and high immune checkpoint expression ( 3 ). The majority of patients have no response or are resistant to the treatment, which is largely associated with cold tumors with few or absence of T cells, low tumor mutational burden, and poor antigen presentation ( 3 ). Furthermore, the efficacy varies among different tumor types, which further complicates treatment strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor-immune relationship plays an important role in tumor development and tumor progression, and tumor immune microenvironment (TIM) is widely accepted as a significant factor influencing therapeutic efficiency of ICB therapy (Song et al, 2020;Wang et al, 2020). Specifically, tumorinfiltrating lymphocytes (TILs) score (Gascón et al, 2020;Hashemi et al, 2021) and PD-L1 status (Wu et al, 2020) were previously suggested as potential biomarkers to be applied in clinical practice for LUAD. However, its translation from bench to bedside is largely limited by the dependence on tissue sample availability and the nonstandardization for evaluation of TIL score and PD-L1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Screening for potentially responsive LUAD patients to ICB therapy before treatment by using an effective immunoligical biomarker is beneficial to remarkably improve the outcome of LUAD patients with ICB therapy (Wu et al, 2020). Tumor-infiltrating lymphocyte (TIL) score and PD-L1 expression in TME are previously suggested as potential biomarkers to select potentially sensitive subpopulation to ICB therapy prior to treatment and to predict survival for LUAD patients (Gascón et al, 2020;Jin et al, 2020;Hashemi et al, 2021). However, evaluations for the status of TIL and PD-L1 are currently non-standardized and limited by tissue samples availability.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that CD4 + T-cells mediate systemic immunity, which is important for long-term tumor elimination ( Wang et al, 2018 ). CD8 + T-cells have the potential not only to recognize, but also to destroy tumor cells ( Gascón et al, 2020 ). Although following CAR modification, cytotoxic CD8 + T-cells mediate the direct eradication of tumor cells, also CD4 + T helper cells (Th cells) have been identified as highly efficient and clinically important T-cells ( Stock et al, 2019 ).…”
Section: T-cells In Cart Therapymentioning
confidence: 99%
“…Recent studies indicate that CD4 + CART cells have a cytotoxic ability comparable to cytotoxic CD8 + CART cells ( Stock et al, 2019 ), and can increase the proliferation of CD8 + T cells ( Yang Y. et al, 2017 ). Based on data inferred from T cell biology, trials have been designed and conducted using defined mixtures of CD8 and CD4 T cells to generate CAR products that have demonstrated success in CD19 + leukemias and lymphomas ( Gascón et al, 2020 ).…”
Section: T-cells In Cart Therapymentioning
confidence: 99%